The influence of early feeding on intestinal development and performance of broiler chickens. Issue 1 (April 2020) - Pakiding, W; Daryatmo,; Ariyani, D; Hardianti,
Abstract: In the first days after hatch, the development of organs such as the gastrointestinal tract, and the growth performance may be affected by the time in between hatch and first feed intake. In current practice, time between hatch and moment of first feed intake may take long time because of variation in hatch time, chick handling, and transportation time. Feed deprivation, especially during the first days after hatch, depresses intestinal development on the short and long term, reflected by a lower intestinal weight, shorter length, lower enzymatic activity, altered villi and crypt cell density, and lower crypt depths and villi heights and finally, depressed growth. The objective of this study was to investigate effects of the moment of first feed intake after hatch on intestinal development and growth performance of broiler chickens. A total 60 unsexed day-old Lohmann broiler chicks were randomly assigned into 3 treatments of 20 chicks each in four replicates (5 chicks each). The treatments were time first feed and water access after hatch, including 12, 42 and 72 hours. Body weight gain and feed intake were recorded weekly and the intestinal development were sampled at 12 days for the measurement of ileum histology and length of gastrointestinal tract. Results obtained were as follows: Time between hatch and moment of first feed intake had no significant effect (P> 0.05) on width of the villi. However, the height of villi, depth of the crypt dan length of the gastrointestinal tract were significantly affected by treatment. The longer delay in the provision of feed and water in day-old chick were lower height of villi and depth of the crypt, dan shorter length of the gastrointestinal tract. Statistically, performance parameters had any difference among treatments, except for feed conversion. The final body weight and feed intake decreased with increasing time between hatch and moment of first feed intake. The results suggest that early delivery of first feed can influence development and growth of gastrointestinal tract. It is also beneficial to improve posthatch growth performance of broiler chickens.